Clinical Features of Patients With COVID‐19 With Nonalcoholic Fatty Liver Disease. Issue 12 (2nd September 2020) - Huang, Rui; Zhu, Li; Wang, Jian; Xue, Leyang; Liu, Longgen; Yan, Xuebing; Huang, Songping; Li, Yang; Yan, Xiaomin; Zhang, Biao; Xu, Tianmin; Li, Chunyang; et al.
Abstract : Previous studies reported that coronavirus disease 2019 (COVID‐19) was likely to result in liver injury. However, few studies investigated liver injury in patients with COVID‐19 with chronic liver diseases. We described the clinical features in patients with COVID‐19 with nonalcoholic fatty liver disease (NAFLD). Confirmed patients with COVID‐19 from hospitals in 10 cities of Jiangsu Province, China, were retrospectively included between January 18, 2020, and February 26, 2020. The hepatic steatosis index (HSI) was used to defined NAFLD. A total of 280 patients with COVID‐19 were enrolled. Eighty‐six (30.7%) of 280 patients with COVID‐19 were diagnosed as NAFLD by HSI. One hundred (35.7%) patients presented abnormal liver function on admission. The median alanine aminotransferase (ALT) levels (34.5 U/L vs. 23.0 U/L; P  < 0.001) and the proportion of elevated ALT (>40 U/L) (40.7% vs. 10.8%; P  < 0.001) were significantly higher in patients with NAFLD than in patients without NAFLD on admission. The proportion of elevated ALT in patients with NAFLD was also significantly higher than patients without NAFLD (65.1% vs. 38.7%; P  < 0.001) during hospitalization. Multivariate analysis showed that age over 50 years (odds ratio [OR], 2.077; 95% confidence interval [CI], 1.183, 3.648; P  = 0.011) and concurrent NAFLD (OR, 2.956; 95% CI, 1.526, 5.726; P  = 0.001) were independent risk factors of ALT elevation in patients with COVID‐19, while the atomized inhalation of interferon α‐2b (OR, 0.402; 95% CI, 0.236, 0.683; P  = 0.001) was associated with a reduced risk of ALT elevation during hospitalization. No patient developed liver failure or death during hospitalization. The complications and clinical outcomes were comparable between patients with COVID‐19 with and without NAFLD. Conclusion: Patients with NAFLD are more likely to develop liver injury when infected by COVID‐19. However, no patient developed severe liver‐related complications during hospitalization.